SPACE ANIMATED WITH THREE DIMENSIONAL STUDIO MAX Edy - Edy Ruslan; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2001)
Animation is a collection of images shown alternately so it looks to move. A collection of pictures from the picture is the frame. Frame is needed in animation applications. Number of frames per-second animation affect the smoothness of movement. Animation of this space is one example of modeling a very simple animation. To create this animation writers using 3D Studio Max as the software. 3D Studio Max is very easy to use and has many facilities and other securities. This animation hopefully useful application for users of computers, especially in the field of multimedia.